Lexique et référence - Palma, Silvia; Frath, Pierre; Hilgert, Emilia; KLEIBER, Georges; Daval, René (Res per nomen, 2020)
The seventh edition of the international symposium "Res per nomen" extended to the whole of the lexicon the reflection on the role of naming in categorization, on the link between meaning, reference and category, on the dynamic construction of meaning in the enunciative and discursive process. This volume includes lexical studies resulting from the confrontation between older or more recent, often opposing, models of analysis of meaning and reference, with the most convincing results. La septième édition du colloque international "Res per nomen" a élargi à l'ensemble du lexique la réflexion sur le rôle de la dénomination dans la catégorisation, sur le lien entre sens, référence et catégorie, sur la construction dynamique du sens dans le processus énonciatif et discursif. Ce volume comprend des études lexicales issues de la confrontation entre des modèles plus anciens ou plus récents, souvent opposés, d'analyse du sens et de la référence, avec les résultats les plus probants.